2008
DOI: 10.1063/1.2841659
|View full text |Cite
|
Sign up to set email alerts
|

Lack of charge offset drift is a robust property of Si single electron transistors

Abstract: One of the challenges that single-electron transistors (SETs) face before they can be considered technologically useful is the charge offset drift. Recently, two different types of Si SETs were shown to have a drift of only 0.01e (the fundamental charge) over several days. Those devices came from one fabrication source. Here, we present the results for Si SETs fabricated by our group (a different source) demonstrating their operation as SETs. We confirm that the charge offset drift is less than 0.01e, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…In contrast, as we have previously shown, 10,13,14 in at least one class of Si-based SET transistors, there is no apparent charge offset drift ͓⌬Q 0 ͑t͒ ഛ 0.01e͔. This fact forms one of the advantages of Si-based SET devices, and one of our aims is to determine how to attain such a lack of long-term drift in the metal-based SET devices.…”
Section: Motivationmentioning
confidence: 87%
“…In contrast, as we have previously shown, 10,13,14 in at least one class of Si-based SET transistors, there is no apparent charge offset drift ͓⌬Q 0 ͑t͒ ഛ 0.01e͔. This fact forms one of the advantages of Si-based SET devices, and one of our aims is to determine how to attain such a lack of long-term drift in the metal-based SET devices.…”
Section: Motivationmentioning
confidence: 87%
“…Given this slight dependence on architecture one might think that the overall stability of devices might be the product of some specific steps in the fabrication. This has been directly addressed in the literature, most directly in reference [47], where devices were fabricated in different foundries. It was found that the stability of all-silicon devices is a robust property of the materials.…”
Section: Silicon-based Devicesmentioning
confidence: 99%
“…It was found that the stability of all-silicon devices is a robust property of the materials. Regardless of how the devices are fabricated, even devices with relatively poor performance (gate leakage and unintentional barriers) exhibit excellent charge offset stability 100 times better than that of metal-based devices [47].…”
Section: Silicon-based Devicesmentioning
confidence: 99%
“…The electron pump used in this study displayed, overall, a remarkable level of stability over many cooldowns and handling procedures. The stability of Coulomb blockade features of silicon single-electron devices is already well-known 17,18 , and we discovered that this stability carries onto high-precision electron pumping. The measurements at MIKES and Aalto showed that a rapid characterisation procedure could yield a pump current accurate to a part per million, on a measurement timescale of roughly 2 days.…”
Section: Discussionmentioning
confidence: 82%